Baseline Frailty Status Influences Recovery Patterns and Outcomes Following Alignment Correction of Cervical Deformity. Issue 6 (20th February 2021) - Pierce, Katherine E; Passias, Peter G; Daniels, Alan H; Lafage, Renaud; Ahmad, Waleed; Naessig, Sara; Lafage, Virginie; Protopsaltis, Themistocles; Eastlack, Robert; Hart, Robert; Burton, Douglas; Bess, Shay; et al.
Abstract: BACKGROUND: Frailty severity may be an important determinant for impaired recovery after cervical spine deformity (CD) corrective surgery. OBJECTIVE: To evaluate postop clinical recovery among CD patients between frailty states undergoing primary procedures. METHODS: Patients >18 yr old undergoing surgery for CD with health-related quality of life (HRQL) data at baseline, 3-mo, and 1-yr postoperative were identified. Patients were stratified by the modified CD frailty index scale from 0 to 1 (no frailty [NF] <0.3,  mild/severe fraily [F] >0.3). Patients in NF and F groups were propensity score matched for TS-CL (T1 slope [TS] minus angle between the C2 inferior end plate and the C7 inferior end plate [CL]) to control for baseline deformity. Area under the curve was calculated for follow-up time intervals determining overall normalized, time-adjusted HRQL outcomes; Integrated Health State (IHS) was compared between NF and F groups. RESULTS: A total of 106 CD patients were included (61.7 yr, 66% F, 27.7 kg/m 2 )—by frailty group: 52.8% NF, 47.2% F. After propensity score matching for TS-CL (mean: 38.1°), 38 patients remained in each of the NF and F groups. IHS-adjusted HRQL outcomes from baseline to 1 yr showed a significant difference in Euro-Qol 5 Dimension scores (NF: 1.02, F: 1.07, P  = .016). No significant differences were found in the IHS Neck Disability Index (NDI) and modified Japanese Orthopedic Association between frailty groups ( P  > .05). F patients had more postop major complications (31.3%) compared to the NF (8.9%), P  = .004, though DJK occurrence and reoperation between the groups was not significant. CONCLUSION: While all groups exhibited improved postop disability and pain scores, frail patients experienced greater amount of improvement in overall health state compared to baseline disability. This signifies that with frailty severity, patients have more room for improvement postop compared to baseline quality of life. Graphical Abstract: